Note on "Modified alpha-psi-Contractive Mappings with Applications": Maher Berzig, Erdal Karapinar - Team, Support (Thai Journal of Mathematics, 2015)
In this short paper, we unexpectedly notice that the modified version of αcontractive mappings, suggested by Salimi et al. [Modified contractive mappings with applications, Fixed Point Theory and Applications 2013, 2013:151] is not a real generalization.